2016
DOI: 10.1097/ccm.0000000000001864
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Brain Injury by Amniotic Mesenchymal Stromal Cell-Secreted Metabolites

Abstract: Human amniotic mesenchymal stromal cell-secreted factors protect the brain after acute injury. Importantly, a fraction rich in metabolites, and containing neither proteic nor ribonucleic molecules was protective. This study indicates the profiling of protective factors that could be useful in cell-free therapeutic approaches for acute brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 83 publications
1
66
0
Order By: Relevance
“…These preclinical studies successfully demonstrated the significant therapeutic properties of hAEC as a candidate stem cell for regenerative medicine. Promising data from in vitro studies that have demonstrated the immunomodulatory properties of hAECs and have prompted a number of preclinical studies using models for lung fibrosis, liver fibrosis, wound healing, arthritis, colitis, multiple sclerosis, graft‐vs‐host disease and brain injury . Decellularized amniotic membrane has also been utilized clinically in the field of ophthalmology as a scaffold for corneal restoration.…”
Section: Therapeutic Potential Of Amniotic Epithelial Cellsmentioning
confidence: 99%
“…These preclinical studies successfully demonstrated the significant therapeutic properties of hAEC as a candidate stem cell for regenerative medicine. Promising data from in vitro studies that have demonstrated the immunomodulatory properties of hAECs and have prompted a number of preclinical studies using models for lung fibrosis, liver fibrosis, wound healing, arthritis, colitis, multiple sclerosis, graft‐vs‐host disease and brain injury . Decellularized amniotic membrane has also been utilized clinically in the field of ophthalmology as a scaffold for corneal restoration.…”
Section: Therapeutic Potential Of Amniotic Epithelial Cellsmentioning
confidence: 99%
“…In this context, even if CB1 did not appear to have any physiological role in controlling interleukin expression and release, the exacerbation of constitutive AEC immunosuppressive activities induced by its pharmacological inhibition opens new biotechnological solutions to potentiate cell-and cell-free-based AEC protocols that have been successfully proposed for the treatment of inflammatory disorders [7,73] such as liver, lung, and tendon fibrosis [31,[74][75][76][77][78][79][80][81][82][83][84]; experimental autoimmune encephalo-myelitis [85]; traumatic brain injury [86,87]; and cardiac ischemia [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…53,55,56 The reduction of iNOS expression and microglia activation could be explained by the presence of anti-inflammatory molecules, 22 including IL-10 and TGF-β 30 in CM-hAMSC. In addition, amnion has been shown to express neurotrophic factors such as BDNF, NGF, and NT-3, 24 and CM-hAMSC contains lysine, taurine, alpha-aminoadipic-acid, and spermidine, 23 HGF, PGE2, angiogenin and leptin, 22 all of which have been reported to possess neuroprotective effects. [25][26][27][28][29][30][31][32][33][34] Mesenchymal stem/stromal cells have become increasingly important for the development of cell-based therapeutics for the treatment of HD.…”
Section: Discussionmentioning
confidence: 99%
“…The medium used as a control (CTRL) was NB/B27 cultured for 5 days. The supernatants were collected, centrifuged, filtered and stored at −80°C until use …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation